Pengaruh Lama Perendaman Dalam Air Kelapa Terhadap Pertumbuhan Bibit Kopi (Coffea sp.) Melalui Stek Batang - Ginting, Ina Febria; Gustian, Meko; Anggara, Heru; Pebriyanti, Pita (Jurnal Sains Agro, 2025)
Coffee is a major agricultural commodity in Indonesia, but its production declined by 1.43% compared to 2021. To boost productivity, vegetative propagation through stem-cutting is a promising method. This study investigates the use of coconut water as a natural plant growth regulator (PGR) to enhance the growth of coffee cuttings. Conducted from June to September 2024 at the Greenhouse of the Faculty of Agriculture, Universitas Pat Petulai, the experiment used a Completely Randomized Design (CRD) with five soaking durations in coconut water: 0 (control), 3, 6, 9, and 12 hours. Results were analyzed using ANOVA and followed by the Least Significant Difference (LSD) test at a 5% significance level. The 9-hour soaking treatment (P3) showed the highest shoot length by the 4th week, while the control had the lowest leaf length. However, soaking duration did not significantly affect shoot diameter, leaf length, or overall shoot growth, indicating a limited influence of coconut water on coffee cutting development